Pengaruh Psikoedukasi dan Terapi Supportif terhadap Pemulihan Pasien Bipolar - Sawdina, Dwi; aulia fadli, septi; royana, ida (Jurnal Pendidikan Transformatif, 2023)
The purpose of this research is to find out the perspective of the "Lebih Baik" youtube channel entitled "Getting to Know Bipolar: A Brief Review of Bipolar Disorder". The journal makes all articles freely available to researchers worldwide, ensuring maximum dissemination of content. Content is published online continuously to provide timely communication to the community and keep publication times to a minimum.In this study, the researcher used a descriptive qualitative method by taking notes because the source of the data was obtained by listening to oral narratives. Whereas in research the cure for bipolar disorder is by means of psychoeducation and supportive therapy through the family is considered to help accelerate bipolar recovery.